Talent Management Practices and Organizational Commitment in Nepalese Commercial Banks - Gautam, Kishor Kumar (KIC International Journal of Social Science and Management, 2022)
The purpose in Nepalese commercial banks. Data was collected from 300 employees working in commercial banks operating in Kathmandu valley using a simple random sampling technique. A structured questionnaire was used for data collection. Model validity and hypotheses were tested using structured equation modelling. Variables reliability and validity are measured by confirmatory factor analysis. The results show that there is a correlation between talent management practices and organizational commitment. The results further show that talent management practices have a significant influence on organizational commitment in commercial banks of Nepal. This study contributes to the literature of talent management practices in financial institutions, especially for the Nepalese scenario.